Filaggrin gene mutations in hand eczema patients in the Indian subcontinent: A prospective case‐control study. (7th March 2019) - Handa, Sanjeev; Khullar, Geeti; Pal, Arnab; Kamboj, Parul; De, Dipankar
Abstract : Background: There are no Indian studies on the association between filaggrin gene ( FLG ) mutations and any dermatosis, including hand eczema. Objectives: To determine the prevalence of FLG mutations in Indian hand eczema patients, and examine associations between such mutations and any aetiological type of hand eczema. Materials and Methods: A total of 163 patients and 86 controls were included. Patients were categorized into aetiological subtypes of hand eczema. FLG polymorphisms (S2889X, 2282del4, R501X, and Q2417X) were determined in patients and controls, and correlated with subtypes. Results: The prevalences of FLG mutations were 33.7% in cases and 3.5% in controls. Mutations in S2889X constituted 96.4% of all FLG mutations. No carrier of R501X and Q2417X mutations was identified. Among 55 patients with mutations, irritant contact dermatitis (ICD) with or without atopy was found in 22 patients, allergic contact dermatitis (ACD) with or without atopy was found in 12, and idiopathic hand eczema was found in 12. There was a significant association of FLG mutations with ICD with or without atopy, ACD without atopy, and idiopathic subtypes. FLG mutations were associated with more severe hand eczema. Conclusions: S2889X mutation is commoner in patients than in controls. FLG polymorphisms are associated with specific subtypes of hand eczema and severe disease.